2013
DOI: 10.1021/ac3029079
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Aminoglycoside–RNA Binding by Localized Surface Plasmon Resonance Spectroscopy

Abstract: RNA is involved in fundamental biological functions when bacterial pathogens replicate. Identifying and studying small molecules that can interact with bacterial RNA and interrupt cellular activities is a promising path for drug design. Aminoglycoside (AMG) antibiotics, prominent natural products that recognize RNA specifically, exert their biological functions by binding to prokaryotic ribosomal RNA and interfering with protein translation, ultimately resulting in bacterial cell death. The decoding site, a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…Most important, the functionalization with receptors imparts specificity by only binding the target analyte with high affinity. In this respect, many different types of biomolecular interactions have been explored using receptors based on antibodies, [4][5][6][7] peptides, 8 aptamers, 9,10 carbohydrates, 11,12 or nucleic acids. 13,14 Colloidal gold particles have interesting optical properties that have been explored in label-free detection schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Most important, the functionalization with receptors imparts specificity by only binding the target analyte with high affinity. In this respect, many different types of biomolecular interactions have been explored using receptors based on antibodies, [4][5][6][7] peptides, 8 aptamers, 9,10 carbohydrates, 11,12 or nucleic acids. 13,14 Colloidal gold particles have interesting optical properties that have been explored in label-free detection schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Tor, Vaskevich, Rubinstein, and co-workers analyzed the interaction of neomycin B with the 16S bacterial ribosomal decoding A site, human ribosomal 18S RNA, and two other constructs using localized SPR (Figures 5b and 7c). 115 Neomycin B had a 10-fold faster k on for bacterial A-site RNA than for human 18S RNA. Authors suggested that this difference in k on might be the basis for preferential binding of neomycin to the bacterial A site over the eukaryotic A site.…”
Section: Example Kinetic Studiesmentioning
confidence: 95%
“…HTS using methods other than fluorescence-based probes, namely MS [125,126], NMR [127] and surface plasmon resonance [128] have also been developed to measure binding affinity for the RNA A-site. Isis Pharmaceuticals has developed a MS assay, which, in addition to determining binding affinities of AGs for RNAs, also identified binding specificity based on the fragmentation pattern of AG/RNA complexes [126].…”
Section: High-throughput Methods To Evaluate New Ags and New Ame Inhibimentioning
confidence: 99%